Impact of drama activities on perceptual-motor skills in early child education - Rojas Castañeda, Manuela (2025)
Bodily expression has been historically consolidated as a key didactical strategy in physical education for developing bodily awareness. In child education, it is essential for acquiring motor skills and abilities that allow children to develop effectively in various contexts. Theater, as a performing art of multidimensional nature, offers a significant potential for the development of perceptual-motor abilities (PMA). This research assessed the impact of a drama intervention in the development of PMA in students aged 5-8 years at the Reggio Emilia School. A quantitative study was implemented with a pre-experimental design in a single group with pre-test/post-test measurements. The sample was made up by 22 students. For the PMA assessment, an evaluation battery was used, specifically designed and validated for the Colombian context. The intervention consisted of a didactic unit structured in eight 60- minute sessions, implemented over four weeks with a frequency of two sessions per week. The drama activities included bodily expression exercises, improvisation, dramatization of stories, role playing and group skits, progressively designed to stimulate the various dimensions of PMA. The statistical analysis was carried out through parametric tests that compared the medians between the pre-test and post-test. The results showed statistically significant improvements (p < .05) in all the variables related to the PMA being assessed. In conclusion, drama constitutes an effective pedagogical tool for promoting the development of perceptual-motor abilities in children, suggesting its systematic inclusion in children’s physical education programs.